2020
DOI: 10.1002/adom.202001764
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Biphenyl‐Diimide Derivatives with Aggregation‐Induced Emission and Thermally Activated Delayed Fluorescence for High Performance OLEDs

Abstract: π‐Conjugated arylene diimide derivatives as a kind of well‐known organic dyes have been widely used as building blocks for constructing n‐type semiconductors. However, the large π‐framework faded their solid‐state emission, which hinders their application in organic light‐emitting diodes (OLEDs). Herein, two novel π‐conjugated donor–acceptor–donor (D‐A‐D) type compounds BPI‐PhPXZ and BPI‐PhDMAC, composed of twisted biphenyl‐diimide (BPI) acceptors and phenoxazine or acridine donors are synthesized. BPI‐PhPXZ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Diimide-based derivatives are known to manifest intrinsic photoluminescence properties and fluorescence detection capability with near unity fluorescence quantum yield. 14,49 In the present work, the emission spectra of the synthesized diimides dyes were simulated at the TD-MN12SX/6-31+G(d) level of theory by applying SMD, the solvation model based on the density of DMF solvent. The radiative lifetime was estimated through the Einstein transition model 50 τ flu = c 3 /(2 × ( E flu ) 2 × f ), in which c stands for the velocity of light in au, E flu is the emission energy in cm −1 , and f is the oscillator strength for the S0 ← S1 transition, based on optimized excited state structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diimide-based derivatives are known to manifest intrinsic photoluminescence properties and fluorescence detection capability with near unity fluorescence quantum yield. 14,49 In the present work, the emission spectra of the synthesized diimides dyes were simulated at the TD-MN12SX/6-31+G(d) level of theory by applying SMD, the solvation model based on the density of DMF solvent. The radiative lifetime was estimated through the Einstein transition model 50 τ flu = c 3 /(2 × ( E flu ) 2 × f ), in which c stands for the velocity of light in au, E flu is the emission energy in cm −1 , and f is the oscillator strength for the S0 ← S1 transition, based on optimized excited state structures.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, diimides, a subclass of rylenes dyes, have tunable electronic properties as well as chemical, thermal, and photochemical stability with near-unity uorescence quantum yields. 14,15 In this context, we report the synthesis and spectroscopic properties of four new symmetrical UV-selective organic dyes based on diimides (DI-CA and DI-N) incorporating carboxyl and pyridyl anchoring groups. Computational quantum chemical investigation was subsequently performed to explore the potential application of the synthesized diimides as photosensitizers in DSCs and as promising cosensitizers of the green-selective BTD-DTP1 organic dye, as reported by Dessì et al 13 Evidently, an entirely organic mix of UV-selective diimides and green-selective BTD-DTP1 dyes would represent a good scenario from a purely environmentally sustainable perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent materials have gained extensive research interest in recent years due to their widespread applications in biological sensing, 1,2 lighting devices, 3,4 stimuli-responsive materials, 5,6 and so on. 7−11 However, traditional fluorophores oftentimes suffer from aggregation-caused quenching (ACQ) effects in condensed states wherein the fluorescence would be quenched precipitously because of the exciton interactions and nonradiative decays.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fluorescent materials have gained extensive research interest in recent years due to their widespread applications in biological sensing, , lighting devices, , stimuli-responsive materials, , and so on. However, traditional fluorophores oftentimes suffer from aggregation-caused quenching (ACQ) effects in condensed states wherein the fluorescence would be quenched precipitously because of the exciton interactions and nonradiative decays. , This issue was subtly addressed when Tang et al reported a completely opposite phenomenon known as aggregation-induced emission (AIE). In such cases, certain fluorogens that emit weakly in dilute solution become highly emissive in the aggregated state on account of the restriction of intramolecular rotation (RIR) …”
Section: Introductionmentioning
confidence: 99%
“…Dyes are based on symmetrical polymethine cyanine, coded VG20-Cx, with x values varying from 2 to 16 carbons on the alkyl chain, and the authors reported PCE of 3.1% and a maximum of 76% average visible transmittance. Diimides, which are part of a larger class of molecules known as rylenes dye, come in symmetrical and asymmetrical forms, depending on how they’re made [ 16 ]. Tunable features of diimides-based derivatives include quantum yields of near-unity fluorescence [ 17 ], and strong electron-accepting properties enable them to be employed as industrial colorants, both as dyes (soluble) and pigments (insoluble) [ 18 ], for the manufacturing of soft electrical devices [ 19 ] and organic electronics [ 20 ].…”
Section: Introductionmentioning
confidence: 99%